Childhood Experiences and Intimate Partner Violence Among Kenyan Males: Mediation by Self-Esteem and Impulsivity - Goodman, Michael (Journal of interpersonal violence, 2021)
This study evaluates associations between childhood social environments and current intimate partner conflict tactics in early adulthood. The subsample for this study (n = 251 men) were participants in a larger community-based study of men’s mental and behavioral health in semirural Kenya. A survey questionnaire was administered by trained interviewers, including validated recall measures from childhood, collective self-esteem and impulsivity, and the conflict tactics scale short form. Analyses utilized regression and mediation methods. The recall measures evaluated the degree of relational warmth and safety recalled from early childhood and forms of abuse, neglect and dysfunction present in the childhood home. Collective self-esteem assessed the perceived value of one’s social groups and one’s value as a member of these groups. Impulsivity measured the propensity to act without thinking. The conflict tactics scale evaluates the presence and frequency of specific behaviors following intimate partner conflict, which lead to two factors—negotiation-based tactics and violence tactics. More early memories of relational warmth, responsiveness, and safety during childhood predict fewer violent intimate conflict tactics. More adverse childhood experiences predict more violent conflict tactics and fewer negotiation-based conflict tactics. Self-esteem and impulsivity mediated associations between recalled childhood experiences and conflict tactics. Further research is required to explore other predisposing factors, psychological processes, and cultural and social norms surrounding the use of violent and nonviolent intimate partner conflict resolution by young men in Sub-Saharan Africa. Violence prevention strategies and policies should explicitly link intimate partner violence prevention with prevention of violence against boys. Interventions should recognize men who perpetrate intimate partner violence are more likely victims of violent childhoods than men who do not perpetrate intimate partner violence. Promoting collective self-esteem and reducing impulsivity among young men may reduce violence against women.